Pengaruh Kepemimpinan Transforrmasional Terhadap Organizational Citizenship Behavior (OCB) Dan Komitmen Organisasi Melalui Kepuasan Kerja Karyawan PT. Bank Panin, Tbk Banjarbaru - Dora Vicky Permatasari; Saladin Ghalib; Irwansyah Irwansyah (JURNAL BISNIS DAN PEMBANGUNAN, 2017)
This study aims to determine the effect of transformational leadership on organizational citizenship behavior and organizational commitment through employee satisfaction PT.Bank Panin, Tbk Banjarbaru. This type of research is explanatory. Population and sample in this study were employees of PT. Bank Panin Tbk branch Banjarbaru with a sample of 32 people and using sampling techniques saturated. The method used is Partial Least Square (PLS). The results showed that 1) the transformational leadership significantly influence organizational citizenhip behavior, 2) Transformational leadership is a significant effect on job satisfaction, 3) Transformational leadership is a significant effect on organizational commitment, 4) Job satisfaction did not significantly affect organizational citizenship behavior, 5) Satisfaction work significant effect on organizational commitment, 6) commitment to the organization significant effect on organizational citizenship behavior, 7) transformational leadership has no effect on organizational citizenship behavior through job satisfaction, 8) transformational leadership is a significant effect on organizational commitment with job satisfaction, 9) job satisfaction influential significantly to organizational citizenship behavior through organizational commitment.Keywords: transformational leadership, organizational citizenship behavior (OCB), organizational commitment, job satisfaction